Understanding Carbon Sequestration in Sugarcane Plant-soil System: Influence of Nutrient Integration Practices in Indo-Gangetic Plains of India - Ajeet Kumar; Sunita Kumari Meena; Sanjay Kumar Singh; S. K. Sinha; Amrita Kumari; A. K. Singh (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
Sugarcane is a versatile crop with significant potential for carbon sequestration in both soil and plants. This study assessed the carbon sequestration in planted sugarcane and rhizospheric soil under various nutrient management practices. According to the IPCC, rising global temperatures due to GHG emissions are a primary cause of global warming. To stabilize global temperatures, it is essential to mitigate anthropogenic CO2 emissions and enhance the sequestration of surplus atmospheric CO2 in plants and soil. Sugarcane cultivation plays a crucial role in this process, as it is a C4 plant with high efficiency in utilizing CO2 during photosynthesis. One approach to enhance CO2 capture is through improved nutrient management practices, which can increase chlorophyll synthesis and nitrogen efficiency in sugarcane. Different treatment compositions can enhance photosynthesis, leading to greater CO2 capture. Consequently, sugarcane crops and their rhizospheric soils act as important carbon sinks, contributing to atmospheric decarbonization and global cooling. Soil Properties and Carbon Storage: The study results indicated that soil physical and chemical properties varied significantly among treatments due to the application of different organic amendments. Soil organic carbon (SOC) was analyzed and ranged from 0.47% to 0.67%. The different organic amendment treatments notably improved soil bulk density, porosity, and carbon storage. Plant Carbon Storage: Carbon stocks in various sugarcane plant parts, including roots, shoots, and leaves, were significantly different across treatments. The highest carbon stock was found in leaves (877.08 kg ha-¹) under T6, followed by roots (668.74 kg ha-¹) in T2, and shoots (422.77 kg ha-¹) in T5. This indicates that leaves stored 30.41% and 107.58% more carbon than roots and shoots, respectively, while roots stored 58.18% more carbon than shoots. The total carbon storage in sugarcane biomass, including aboveground and belowground parts, varied significantly across treatments. The mean carbon storage in aboveground parts (leaves and stalks) was significantly higher (1239.65 kg ha-¹) than in underground parts (roots) at 621.73 kg ha-¹. These findings demonstrate that sugarcane farming practices can effectively enhance carbon sequestration, contributing to climate change mitigation. The sugarcane crop and rhizospheric soils act as important carbon sinks in the decarbonisation of the atmosphere, ultimately reducing carbon levels and causing global cooling.